Physiology and energetics of the sandy-beach bivalve Donax serra Röding with special reference to temperature and chlorine tolerance - Stenton-Dozey, Jeanette Mary Edgeworth (Department of Biological Sciences, 2015)
Bibliography: pages 287-318.